75.0k views
2 votes
Given both, find (f-g)(x)

Given both, find (f-g)(x)-example-1
User Lilbeth
by
5.1k points

1 Answer

2 votes


\mathfrak{\huge{\orange{\underline{\underline{AnSwEr:-}}}}}

Actually Welcome to the concept of Functions.

Here, we are given with,

f(x) = 4x + 4 and g(x) = 5x - 8

hence, now we have time get (f-g) (x)

so we get as,

==> (f-g) (x) ==> f(x) - g(x)

===> 4x + 4 - (5x - 8)

==> 4x + 4 -5x +8

==> -x + 12

==> hence, 12 - x

so we get as,

(f-g) (x) ==> 12 - x

User Anudeepks
by
5.2k points